Case on Managing Multi-Projects in Process Industry - M., Waris (Penerbit UMP, 2017)
Multi-project management or Program Management is defined as the centralized coordinated management of group of related projects or similar works to achieve the strategic benefits and objectives. It may optimize schedule across the program, deliver incremental benefits, as well as rationalization of manpower. This case is related to the successful planning and execution pf rehabilitation projects of National Steel Corporation. Here the aim is to integrate multiprojects in the form of a program for the best use of resources and expertise.